Enterovirus Infections in Solid Organ Transplant Recipients: a Clinical Comparison from a Regional University Hospital in the Netherlands - Hayley Cassidy; Coretta van Leer-Buter; Hubert G. M. Niesters (Microbiology Spectrum, 2022)
ABSTRACT Enterovirus infections are known to cause a diverse range of illnesses, even in healthy individuals. However, information detailing enterovirus infections and their severity in immunocompromised patients, such as transplant recipients, is limited. We compared enterovirus infections in terms of genotypes, clinical presentation, and severity between transplant and nontransplant patients. A total of 264 patients (38 transplant recipients) with 283 enterovirus infection episodes were identified in our hospital between 2014 and 2018. We explored the following factors associated with enterovirus infections: clinical presentation and diagnosis on discharge, length of hospital stay, symptom persistence, and infection episodes in both children and adults. We observed some differences in genotypes between patients, with enterovirus group C occurring mainly in transplant recipients (P < 0.05). EV-associated gastrointestinal infections were more common in patients with a transplant (children [71%] and adults [46%]), compared to nontransplant patients (P < 0.05). Additionally, nontransplant patients had a higher number of hospital stays (P < 0.05), potentially reflecting more severe disease. However, transplant patients were more likely to have symptom persistence after discharge (P < 0.05). Finally, children and adults with a transplant were more likely to have additional enterovirus infection episodes (P < 0.05). In our cohort, enterovirus infections did not seem to be more severe after transplantation; however, patients tended to present with different clinical symptoms and had genotypes rarely found in nontransplant recipients. IMPORTANCE Despite the high prevalence of enteroviruses in the community and the increasing demand for transplants from an aging population, knowledge on enteroviruses in solid organ transplant recipients is currently limited. Transplant recipients represent a significant patient population and require additional considerations in patient management, particularly as they have an increased risk of disease severity. Enteroviruses are known to cause significant morbidity, with a diverse range of clinical presentation from over 100 different genotypes. In this study, we aimed to provide a more comprehensive overview of enteroviral infections in transplant recipients, compared to nontransplant patients, and to bridge some gaps in our current knowledge. Identifying potential clinical manifestation patterns can help improve patient management following enterovirus infections.